Understanding Luigi Pirandello - Bassanese, Fiora A. (Understanding modern European and Latin American literature., 1997)
In this introduction to the life and literary contributions of a Nobel Prize winner and one of Italy's most distinguished writers, Fiora A. Bassanese surveys the stories, novels, and plays of Luigi Pirandello and evaluates the significance of his influence on twentieth-century literature. Describing Pirandello as a prototypical modernist, Bassanese traces his artistic development from his early roots in Sicilian provincialism and positivist thought to his attainment of international fame as an innovative dramatis and a thought-provoking narrator. She contends that his works helped to bring an end to nineteenth-century optimism. They transformed Italian theater and fiction by catapulting both into the modern era.